Morphological development of Hilsa shad [Tenualosa ilisha (F. Hamilton, 1822)] larvae from Meghna Estuary, Bangladesh - Riar, Md. Golam Sajed (2018)
Hilsa shad (Tenualosa ilisha) locally familiar as ilish or hilsa is a national fish of Bangladesh. Despite its popularity, many biological aspects of this fish are still unknown. Morphometric characteristics, mouth and gut morphological development are the important factors to be identify the fish larvae and informs us the type of foods taken as well as its feeding range. In larval fish, the food size and types is closely related with the mouth and gut morphology. So far, there was limited information available on hilsa larvae identification and no information available on larval mouth and gut morphology of Hilsa shad, which are the limiting factor for its own larvae culture and rearing. Therefore, this study was conducted to identify the hilsa larvae based on its morphomeristic characteristics and observe the morphological changes of mouth and gut during different larval stages of T. ilisha. Methodology of this study was different from other larval study. For this study larvae was collected by sampling from the wild breeding and nursing ground, not from hatchery breeding. Weekly sampling was performed to collect the sample from Meghna estuary, Bangladesh between August 2016 and January 2017. Collected samples were preserved in 5% formalin and transported to the laboratory. Morphological characteristics of the larvae and the mouth and gut morphology of larvae and early juvenile stages were examined using Keyence Digital Microscope (VHX-500). Larvae of T. ilisha were characterized by their distinguished elongated body, moderately high numbers of myomere; small to moderate mouth, short-based dorsal and anal fin (never overlaps the anal fins). The body depth increased more than body length at metamorphosis stage (larvae to juveniles). The smallest mouth size was found at 45ᴼ mouth gap while largest found was at 90ᴼ. It was observed that the length of lower jaw was higher than the upper jaw length. There were four larval stages observed in this experiment viz. yolk sack stage, pre flexion stage, flexion stage, post flexion. The mouth was initially closed at yolk sac stage. In pre flexion stage, the mouth gap of the larvae ranged between 177 ± 25 and 367 ± 47 μm, while in flexion stage it ranged between 241 ± 31 and 497 ± 59 μm. As for post flexion stage, it ranged between 307 ± 38 and 621 ± 74 μm and in early juvenile stage it ranged between 393 ± 61 and 788 ± 119 μm. It is revealed that there was a significant relationship between standard length (SL) and upper jaw length (R2 = 0.941, P < 0.05) similarly with the lower jaw (R2 = 0.931, P < 0.05). Significant relationship was also found between SL and mouth gap at 90ᴼ (R2 = 0.938, P < 0.05). Digestive tract was transparent and formed a straight tube at the yolk sac stage. At pre flexion stage, the digestive tract was differentiated into mouth opening, buccopharyngeal cavity, oesophagus, stomach, intestines and rectum. Development of digestive tract was almost completed during pre flexion stage. The length of the digestive tract did increase along with the length of the body. During pre flexion stage, food particles were observed in the gut of the larvae. Gut loop was clearly observed at post flexion stage. The percentage of gut length compared with the standard length was 84.87 ± 4.87%, 85.64 ± 4.47%, 82.29 ± 6.18%, 77.99 ± 4.98%, 74.02 ± 3.27% at yolk sac, pre flexion, flexion, post flexion and juvenile stages, respectively. There was a strong linear relationship between the gut length and standard length (R2= 0.97, p < 0.05). This study was a first attempt which investigated the mouth and gut morphological changes of hilsa larvae collected from the Meghna estuary, Bangladesh. Overall, these finding can be used to identify the hilsa larvae in wild and considered base line information for size and types of larval food in culture and management of T. ilisha.